Tribes of India : ongoing challenges - Mann, Rann Singh, 1936- (New Delhi : MD Publications, 1996)
Contributed articles.
Keywords: Ethnology -- India; India -- Social life and customs; India -- Social conditions -- 1947-; 68-92